Teaching and public school daily life: influences on the teacher's mental health (Research, Society and Development, 2020)
Conflict situations between individuals and their work experiences, such as encouraging competition, demanding strict deadlines, low pay and overwork, can lead to the risk of psychological distress. In this sense, it is observed that teachers suffer several demands that can interfere in their work process, thanks to the adversities of the school routine that directly affect their mental health. The research sought to understand the influences of performance in elementary education on the teacher's mental health. The study included 10 teachers from the early years of elementary school in municipal schools in Niterói / RJ. It is a qualitative research, a case study type. To achieve the proposed objectives, a semi-structured interview was conducted. Data analysis was obtained based on Bardin's content analysis. The results showed that the teaching profession and the school routine, have characteristics that can directly affect the well-being and influence the mental health of this worker, triggering psychological suffering such as: stress, tiredness, fatigue, anguish and despair. It was also demonstrated that the interferences of the lack of family participation in the human and school development of students, directly influence the school dynamics. It is important to develop strategies for the promotion and prevention of mental health, as this phenomenon can affect teacher well-being, generating cases of absenteeism and absence from work.